Paciente de sexo femenino de 64 años de edad que presenta un diagnóstico de diabetes mellitus tipo ii y sobrepeso. - Baño Baño, Dayana Katherine (2019)
Diabetes is defined as a chronic non-communicable disease that is caused by the continuous increase and elevation of blood glucose above normal values. In the following study, the general objective was to elaborate an adequate nutritional plan for the pathology of the patient with Type II Diabetes Mellitus and overweight. An observational and descriptive methodology was used to develop this clinical case, taking into account the clinical history, food history, clinical examination and biochemical tests. The present case study is based on a 64-year-old female patient who was diagnosed with Diabetes Mellitus II and Overweight with a moderate cardiovascular risk, related to poor eating habits, evidenced in the 24-hour reminder which shows the excess carbohydrates, fats and sweeteners. Finally, a food plan of 1600 kcal / day, low fat, low sodium, high fiber, divided into 5 meals a day, is carried out, the following study concludes with favorable results in their biochemical tests and body weight reflecting a normal BMI.